Expert System Eating Disorder To Youth With The Hybrid Method - Yenila, Firna; Wiyandra, Yogi (Sinkron : jurnal dan penelitian teknik informatika, 2019)
The research aims to provide information for the wider community about bulimia nervosa that often afflicts the community especially teenagers. Bulimia nervosa is one type of psychiatric disorder that is habitual that has ingrained from the community itself. No people understand the symptoms or indications of eating disorder in adolescents, and not infrequently among sufferers not doing direct treatment or looking for a direct solution to this disorder. To communicate with doctors also have constraints with time and confusion about what is to be conveyed. Expert system is a solution, this system is able to provide information to researchers about eating disorders in adolescents and provide solutions like a doctor or nutrition expert. It was built using by hybrid method which combines certainty factors and forward chaining.